ANALISIS INPUT-OUTPUT PADA STRATEGI PEMULIHAN PEREKONOMIAN, PENYERAPAN TENAGA KERJA DAN PENINGKATAN PENDAPATAN DALAM MENGATASI DAMPAK COVID-19 DI PROVINSI NTT - Kristanto Setyo Utomo (Badan Pusat Statistik Provinsi NTT, 2021)
The Covid-19 pandemic in Indonesia since the beginning of 2020 has had a negative impact, especially on the economic sector. Various policies to limit mobilization and community activities in preventing the spread of Covid-19 have caused the economy of East Nusa Tenggara Province to enter a recession zone in 2020. The government has tried to encourage the process of National Economic Recovery (PEN) through various policies. This study implements input-output analysis in supporting the policy to accelerate PEN through determining the priority of sectors that have the most significant impact on increasing economic growth, employment, and increasing incomes. This study indicates that encouraging an increase in final demand in the electricity, gas, and water sector will have the most significant multiplier impact on economic growth in the Province of NTT. To increase employment opportunities, the government needs to focus on increasing the output of the manufacturing sector, which will have the highest employment absorption compared to other sectors. Meanwhile, to increase income, spending on the final demand for the education sector by both the government and households will significantly impact increasing people's income in the NTT Province.